Vulvodynia: Up to date - Matzumura-Kasano, Juan P. (2018)
Vulvodynia is defined as vulvar discomfort, described as a burning pain with an average duration of 3 months and a prevalence of 16%. The methodology used consisted of a systematic review and analysis in electronic databases, through the use of keywords. The etiology remains unknown, despite the fact that various theories maintain that it has a multifactorial origin. The diagnosis of vulvodynia is made through a thorough evaluation of the history of pain, sexual history, clinical situation and physical examination. Non-medical treatment includes psychological interventions that aim to reduce pain and restore sexual function. Alternative therapies have not yet proven effective for the treatment of vulvodynia, while physical therapy, by helping to reduce tissue restrictions, helps restore the length of the muscles and tissues of the pelvis. Likewise, medical treatment includes local therapy, through the use of antinociceptives, anti-inflammatory agents and neuromodulators; It also uses tricyclic antidepressants, norepinephrine and anticonvulsants. Surgical treatment has been shown to be a strategy to reduce pain and the surgeon's experience should be taken into account as a determining factor. In conclusion, vulvodynia is a health problem for women that affects their sexual function, quality of life and treatment must be approached with a holistic and multidisciplinary approach.